Keterampilan Menulis Puisi Melalui Model Problem Based Learning Pada Siswa SMP - Zulfa Kamila; Ika Septiana; Azzah Nayla (Departement of Mathematics Education, 2023)
The purpose of this research is to describe poetry writing skills that are applied to junior high school students, which are expected to improve learning outcomes and students' critical thinking skills. This type of research is classroom action research. The data in this study are student learning outcomes taken using test and non-test techniques. The test technique was carried out in the form of an essay question which consisted of 1 question, and non-test techniques which consisted of observation, interviews, and questionnaires, before the problem based learning model was applied, students' knowledge of poetry and student scores were still very low. Through the problem-based learning model, students find it easier to participate in learning to write poetry, find it easier to find imagination, and student scores rise above the KKM, which initially scores below 70. After applying the problem-based learning model, student scores rise above the KKM and the average grade students to 76.